PELATIHAN PEMANFAATAN LIMBAH BIJI DURIAN MENJADI SUSU BIJI DURIAN (SUBIDUR) DI DESA TEWANG TAMPANG - Mohammad Jamaludin; Afifah Nurul Humam; Ahmad Maranata; Aulia Ramadhanti Safitri; Ervina Kusuma Ningrum; Hamelia Putri; Ilham Gede Pangestu; Juwita Juwita; Maulya Ulfah; Muhammad Abijar Gifari; Nur Hakikiy (LOGISTA - Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Organic waste of durian seeds that are often discharged in the Katingan River, causing pollution and disruption of the water ecosystem. Therefore, the need for the use of durian seeds into UMKM products that are useful and have a high value. In accordance with the purpose of this training is to foster the interest of housewives in processing durian seeds into durian seed milk food products that are useful and can improve the household income. The methods in this training are the observation stage, the material presentation stage, discussion and question and answer, the demonstration stage and the direct mentoring stage. The result of the durian seed milk training is that housewives have a high interest in processing durian seeds as waste, in accordance with the purpose of the training, which is to foster the interest of household in processing durian seeds into durian seed milk food products. Keyword: Durian seeds, housewives, durian seed milk